Landscape Design as the Representation of Relationships with Nature, Ecologies and Other Living Species - Lucina Caravaggi (Diségno)
Landscape design has always been considered an open reference, an available space of interpretation, but this is not equivalent to considering it a field of indeterminate images and concepts [Caravaggi 2021]. The hypothesis I will attempt to argue in this article is that landscape design can be coherently interpreted as a representation of the infinite relationships between human societies and the natural world and, more recently, between humans and other living species. [read more]